Grãos secos de destilaria com solúveis na alimentação de codornas de corte - Moreno, Fanny Leonila Velasquez (2021)
Dried distillers grains with solubles(DDGS), a co-product from biofuels industry resulting from the cereal fermentation process for ethanol production, can provide satisfactory amounts of energy and nutrients for animal feed. Therefore, its use in animal nutrition depends basically on knowledge about chemical composition, digestibility of nutrients, anti-nutritional factors and availability of the co-product on the market. In this sense, the objective of this study was to determine the nutritional value of DDGS for male and female meat-type quails (Exp. I), and to evaluate the effects of the inclusion of DDGS in the beef quail diet on the performance, carcass characteristics, meat quality, gastrointestinal morphometry and economic viability (Exp. II). In experiment I, 72 birds were used in a completely randomized design, with two treatments, six replicates and three birds per experimental unit, using the total excreta collection method. The experimental diets consisted of a reference diet and a test diet with isometric replacement of 200 g kg-1 of the reference diet by DDGS. There was no difference between males and females (P > 0.05) for the metabolizability coefficients of dry matter, crude protein, ether extract and insoluble fiber in neutral detergent and for the retention coefficients of mineral matter and total inorganic phosphorus. While the values of apparent metabolizable energy corrected by nitrogen balance of the DDGS were 2,485 kcal kg-1 for males and 2,464 kcal kg-1 for females respectively. In experiment II, 432 birds from with 1 day of age were, distributed in a completely randomized design, with six levels of DDGS in the diet (0, 50, 100, 150, 200 and 250 g kg-1 ), six replicates and 12 birds per experimental unit, totaling 36 experimental units. At the end of the breeding period, carcass characteristics, gastrointestinal morphometry, meat quality and economic viability were evaluated. In the final phase (22 to 42 days) and in the total period (1 to 42 days), feed intake increased linearly (P = 0.015 and 0.040) and feed conversion worsened (P = 0.038 and 0.001) with the inclusion of DDGS, respectively. An increasing linear effect (P = 0.001) was observed for the relative weight of the gizzard and a decreasing linear effect for the gross aggregate value (P = 0.032) and profitability index (P = 0.001) with the increase in DDGS levels. It is concluded that the values of apparent metabolizable energy corrected by the nitrogen balance of the DDGS for male and female broiler quails is 2,419 kcal kg-1 . Levels of up to 250 g kg-1 of DDGS in the diet of beef quails do not affect growth, carcass characteristics and meat quality. However, considering the increase in feed consumption and worsening of feed conversion in the 22 to 42 day phase and in the 1 to 42 day period, the prices of the other ingredients in the harvest and off-season must be considered to determine the level of inclusion of DDGS in the diet.